PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG USAHA, PERPUTARAN PERSEDIAAN DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN - Neneng Sri Suprihatin; Etty Nasser (Universitas Serang Raya, 2016)
The purpose of this study is to determine the effect of cash turnover, account receivable turnover, inventory turnover and leverage to financial performance (Liquidity and Rentability). The independent variable is cash turnover, account receivable turnover, inventory turnover and leverage. The dependent variable are financial performance (Liquidity and Rentability). The sample used in the study consists of manufacturing company in food and beverage sector the period of 2009-2012.The result show that cash turnover, account receivable turnover, leverage significant effect to financial performance in liquidity and rentability and then inventory turnover no significant to financial performance in liquidity and rentability. Keyword : Cash turnover, Account receivable turnover, Leverage, financial performance (liquidity and rentability).